The Hypoxic Microenvironment of Breast Cancer Cells Promotes Resistance in Radiation Therapy - Gilreath, Cordell; Boerma, Marjan; Qin, Zhiqiang; Hudson, M. Keith; Wang, Shanzhi (Frontiers in Oncology, 2021)
The American Cancer Society has estimated an expected 279,100 new breast cancer cases, and an expected 42,690 breast cancer deaths in the U.S. for the year 2020. This includes an estimated 276,480 women who are expected to be diagnosed. Radiation therapy, also called ionizing radiation therapy, is one of the most frequently used methods in the treatment of breast cancer. While radiation therapy is used in the treatment of more than 50% of all cancer cases, tumor resistance to ionizing radiation presents a major challenge for effective cancer treatment. Most tumor cells are in a hypoxic microenvironment that promotes resistance to radiation therapy. In addition to radiation resistance, the hypoxic microenvironment also promotes cancer proliferation and metastasis. In this review, we will discuss the hypoxic microenvironment of breast cancer tumors, related signaling pathways, breast cancer stem-like cells, and the resistance to radiation therapy. Recent developments in our understanding of tumor hypoxia and hypoxic pathways may assist us in developing new strategies to increase cancer control in radiation therapy.